Refining the sleep disturbance scale for children: A psychometric study in an Indian pediatric population - Nair, Lekshmy S. R.; George, Sageena; Nujum, Zinia Thajudeen; Anandaraj, S.; Geetha, S.; Salim, Shiad (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2025)
ABSTRACT Objective: This study aimed to develop a simplified version of the Sleep Disturbance Scale for Children (SDSC) by evaluating expert consensus on content validity and factorial alignment. The primary goal was to retain essential items while ensuring practicality for clinical and research use in pediatric populations, especially in dentistry. Methodology: A panel of experts assessed 26 SDSC items using various psychometric measures, including Content Validity Ratio (CVR), Item-level Content Validity Index (I-CVI), Factorial Validity Index (FVI), Inter-rater Agreement (IRA), and Fleiss' Kappa. Items were evaluated for relevance, clarity, and alignment with theoretical domains. The items that demonstrated strong validity, expert agreement, and alignment were retained, while those with lower scores or cross-domain overlaps were considered for exclusion. Results: The analysis revealed high content validity, with most items achieving CVR and I-CVI values above the acceptable thresholds. The FVI indicated strong factorial validity across all domains, with no major discrepancies in domain assignments. IRA and Fleiss' Kappa further confirmed the consistency of expert ratings. A simplified version of the SDSC was developed, retaining core items addressing sleep latency, night awakenings, breathing disturbances, and daytime somnolence. Conclusion: This study provides a refined version of the SDSC with improved psychometric properties, suitable for pediatric dentistry applications. The simplified tool ensures that relevant sleep disturbances are effectively captured, offering a practical screening tool for clinicians in both pediatric and dental settings. The findings underline the importance of expert consensus in developing valid and reliable tools for the assessment of pediatric sleep disorders.